Persepsi Ibu Hamil Tentang Donor ASI di Margadana Kota Tegal (PROFESSIONAL HEALTH JOURNAL, 2023)
Exclusive breastfeeding is the first choice for infant nutrition. Breast milk produced by the mother and contains all the nutrients needed by the baby for the growth and development needs of the baby. But not all mothers are able to give breast milk because of certain needs. Breast milk donors become an option in these conditions. Breast milk donors are not very popular in developing countries like Indonesia. This study discusses the perception of pregnant women about breastfeeding donors as an effort to look for information on breastfeeding donors to the community. By using descriptive research and quantitative learning for 36 pregnant women. The results showed that most pregnant women had good knowledge about exclusive breastfeeding (91.7%), all pregnant women (100%) have a commitment to provide exclusive breastfeeding and have positive perceptions about breastfeeding donors (83.3%). Need help and institutions related to the implementation of breastfeeding donors to avoid uncontrolled breastfeeding assistance.